2010
DOI: 10.1007/s00330-009-1528-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary giant cell tumor of soft tissue: fluid-fluid levels at MRI (2010:3b)

Abstract: GCT-ST should be included in the differential diagnosis of soft tissue tumors with FFLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hu et al reported the tumor exhibited predominantly slight hyperintensity on T2 images and intensely heterogeneous enhancement on contrast-enhanced T1-weighted images [ 6 ]. Moris reported a case with a hypointense rim on T2-weighted images [ 9 ]. In our MRI, the viable solid lesion was shown as the lower intensity of T2-weighted images, and the necrotic lesion was shown as irregular shape of isointensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported the tumor exhibited predominantly slight hyperintensity on T2 images and intensely heterogeneous enhancement on contrast-enhanced T1-weighted images [ 6 ]. Moris reported a case with a hypointense rim on T2-weighted images [ 9 ]. In our MRI, the viable solid lesion was shown as the lower intensity of T2-weighted images, and the necrotic lesion was shown as irregular shape of isointensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, primary GCT-ST mainly affects young to middle-aged adults[ 4 - 11 , 16 ]. Here, our patient was a young woman who had an ill-circumscribed multinodular mass covered by a fleshy red-brown surface and pain in the upper limb.…”
Section: Discussionmentioning
confidence: 99%
“…On histopathology, soft tissue ABCs usually contain more reactive osteoid and woven bones, but fewer giant cells than a giant cell tumor of soft tissue or giant cell tumor of the tendon sheath. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%